Effect of Different Combinations of Unboiled and Boiled Tomato Waste in Diet on Performance, Internal Organ Development and Serum Lipid Profile of Broiler Chicken - Mahata , Maria Endo; Manik, Jamaluddin; Taufik, Muhammad; Rizal, Yose; Ardi, (International Journal of Poultry Science, 2016)
Owing to the beneficial effects of a carotenoid called lycopene in tomatoes, the present work was undertaken to study the effect of dietary unboiled (UT) and boiled tomato (BT) waste in broiler chicken on performance, internal organ development and serum lipid profile. One hundred fifty Arbor Acress strain broiler chicken of one week age were used for the study. The experiment was performed in a completely randomized design with different combination of UT and BT (0% UT: 0% BT; 25% UT: 75% BT; 50% UT: 50% BT; 75% UT: 25% BT; 100% UB and 100% BT) to completely replace rice-bran and altering the levels of yellow corn and coconut oil in diet. Each treatment was repeated five times. The results revealed that feed consumption, daily weight gain and feed conversion of broiler chicken were not significantly (p>0.05) affected by various dietary combinations of UT and BT waste. The weights of said internal organs of broiler chicken did not vary significantly (p>0.05) by various combination of dietary UT and BT waste. Further, except for HDL, there was a significant (p